Prerequisites for HACCP in small-scale poultry production in Maputo, Mozambique - Muchangos, A.C.; McCrindle, C.M.E.; Matusse, H.; Makita, K.; Grace, Delia (2011)
BACKGROUND: In Mozambique, the risk to human health of consuming poultry meat obtained from both the formal and informal market is unknown. Poultry is a major component of the diet and a valuable and affordable source of protein for all levels of society in Mozambique, because red meat is expensive. However, diarrheal diseases remain an important cause of mortalities, and it is unknown whether poultry meat consumption contributes to this. This study investigated and described the value chains for poultry production in Maputo, indicating possible stages at which there is a risk of microbiological hazards that could influence safety and quality of the final product. METHODS: The magnitude of this risk was estimated using participatory microbiological risk assessment. For this purpose, a total of 330 samples of poultry meat from freshly slaughtered and frozen fowls were randomly collected from formal abattoirs (n=110), live bird markets (n=110) and farms (n=110). The following microbial monitoring tests using 3M™ Petrifilm™ Plates were analysed: E coli Type I, Coliforms and plate count as indicators of contamination to assess the compliance with Good Hygiene Practices (GHP) and Good Manufacture Procedures (GMP) that were considered relevant pre-requisites for Hazard Analysis Critical Control Point (HACCP). RESULTS: The contamination rate with E. coli Type I was significantly higher in live bird markets (69/110, 63%) than carcasses from the formal abattoir (43/110, 39%, x2=11.4, df=1, p<0.001) and farms (44/110, 40%, x2=10.5, df=1, p=0.001). SUMMARY: The results suggested that poultry meat from live bird markets was more risky than poultry purchased from the formal sector or direct from the farm. A hygiene assessment system is proposed for all three value chains with a focus on those critical control points identified during the study. Participatory risk assessment has been carried out with poultry meat processors, to improve the quality and safety of poultry meat and develop integrated food chain hygiene management systems appropriate for the poultry sector in Mozambique.